Analysis of Flour Inventory Control Strategy as Raw Material for Shrimp Crackers Using Markov Chain - Sukmono, Tedjo; Hartanti, Lusia Permata Sari; Murnawan, Hery; Jamaluddin, Jamaluddin (Widya Teknik, 2025)
Abstract: One of the important challenges the industry faces is the problem of raw material inventory, so good inventory management is essential. This management results in the emergence of inventory costs comparable to the company's operational costs. Inventory deviations in an industry can be in the form of less or more inventory caused by inaccurate inventory calculations, such as those experienced by PT SLU. The condition of PT SLU shows that the products produced have decreased while raw materials have an excess inventory of more than 15,000 kg. This study aims to determine the quantity of flour raw materials to achieve optimal inventory costs at PT SLU. The method used is the Markov chain and enumeration method to determine the optimal amount of raw materials to reduce costs. The research findings indicate that policy 58 yields the lowest expected cost of Rp. 32,463,360 compared to other policies. Therefore, it is suggested that improvements be implemented, such as if the system is in states 3, 4, 5, or 6, for long-term policy. This condition can help companies create strategies to reduce overstock, particularly of raw flour materials.